Jugamos a ser maratonistas - Pulache Ventura, Jessica Yulimar (2020)
The work of professional sufficiency had the title: "Let's play marathoners." The design of the learning activity, the research of theoretical support and pedagogical support, have been developed based on bibliographic references, as well as on the application of the knowledge acquired, during the years of my professional training and according to my work experience with the children of the initial education level. The competence that was developed in this activity was: Recognize your bodily sensations and identify the needs and changes in the state of your body, such as breathing and sweating. He recognizes the parts of his body by relating them to his actions and naming them spontaneously in different everyday situations, corresponding to the area of psychomotor skills. I considered that the purpose of the activity is, that the children recognize the changes of their body through breathing and sweating when playing to be a marathon runner. In this way, the capacity of the area was taken into account: - Expresses itself bodily. - Understands your body. Children must understand that psychomotor activities are important in the learning development, because it allows them to develop all their senses through the movement and manipulation of the material presented and adapted according to the purpose of the learning session, also through these activities they learn to recognize its changes that the body manifests in different game situations.